“Jongeren met toekomstplannen”: Het verhaal van Abu Muhammed over standvastigheid, rechtvaardigheid en jihad - de Koning, Martijn (Religie & Samenleving, 2015)
Since 2012 about 250 Dutch Muslims have joined Islamic State (IS), Jabhat al-Nusra and other factions in the Syrian civil war. Much of the debates concerning these foreign fighters has revolved around the question: why do they go? Certainly in public debates the motives as explained by the foreign fighters themselves are taken for granted. In this article I will propose a different approach of these motives. I will argue that they should not be seen as causal factors explaining why people join the war but as stories through which they explain, legitimize and rationalize their choices and through which they construct and perform their identity. I will do this by analysing three types of narratives (socio-emotional, socio-political and religious-ideological) that constitute the life story of Abu Muhammed; one of the Dutch foreign fighters. I will show how, within a particular socio-political context, he constitutes himself as a steadfast Muslim fighter.